Production of a modified peptide clavanin in Pichia pastoris: cloning, expression, purification and in vitro activities - Mulder, Kelly Cristina (AMB Express, 2015)
Antimicrobial peptides are one of the most promising peptide-based drugs due to their enormous potential as novel biopharmaceuticals in both human and animal industries. In order to develop strategies to over produce such molecules, heterologous production of a modified version of clavanin A, here named clavanin MO (clavMO), was successfully achieved in the methylothopic yeast Pichia pastoris. ClavMO was fused to thioredoxin as a carrier protein and the construction was tested using two promoters, P(AOX1) and P(GAP), based on either induced or constitutive expression systems, respectively. After growth in 5 L Bioreactor, clavMO-thio was recovered and purified through size exclusion chromatography. Our findings show that both constitutive and inducible expression systems produce active clavMO fused to thioredoxin against both Gram-negative Klebsiella pneumoniae and Gram-positive Staphylococcus aureus microorganisms. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13568-015-0129-0) contains supplementary material, which is available to authorized users.